(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the multicultural and interconnected society, digital technology has become an essential pedagogical tool for teachers in rural areas, whose fundamental task is to integrate digital technology into the educational context. This study analyzes and evaluates the self-perception of teachers about their digital competence and the relationship with their performance in the intercultural environment of rural secondary education. The research approach was quantitative, non-experimental descriptive-correlational design, with a sample of 192 rural secondary education teachers from Huánuco-Peru, using the survey technique through the questionnaire instrument, validated by expert judgment. The results indicate that the digital competence and intercultural vision of teachers in rural areas is direct, on average more than 58% assume to have developed their digital competence at a high or very high level, while more than 71% have a positive perception about intercultural education; the Spearman correlation coefficient between the two variables is 0.75. It is concluded that there is a direct and complementary relationship between the development of digital competence and the interculturality of teachers, which leads to an efficient management of the teaching-learning process.